Trichoderma volatiles effecting Arabidopsis: from inhibition to protection against phytopathogenic fungi - Kottb, Metwally; Gigolashvili, Tamara; Großkinsky, Dominik K.; Piechulla, Birgit (Frontiers in Microbiology, 2015)
Trichoderma species are present in many ecosystems and some strains have the ability to reduce the severity of plant diseases by activating various defence pathways via specific biologically active signaling molecules. Hence we investigated the effects of low molecular weight volatile compounds of Trichoderma asperellum IsmT5 on Arabidopsis thaliana. During co-cultivation of T. asperellum IsmT5 without physical contact to A. thaliana we observed smaller but vital and robust plants. The exposed plants exhibit increased trichome numbers, accumulation of defence-related compounds such as H2O2, anthocyanin, camalexin, and increased expression of defence related genes. We conclude that A. thaliana perceives the Trichoderma volatiles as stress compounds and subsequently initiates multilayered adaptations including activation of signaling cascades to withstand this environmental influence. The prominent headspace volatile of T. asperellum IsmT5 was identified to be 6-pentyl-α-pyrone, which was solely applied to A. thaliana to verify the growth and defence reactions. Most noticeable is that A. thaliana preexposed to 6PP showed significantly reduced symptoms when challenged with Botrytis cinerea and Alternaria brassicicola, indicating that defence-activated plants subsequently became more resistant to pathogen attack. Together, these results support that products that are based on Trichoderma volatiles have the potential being a useful biocontrol agent in agriculture.